N-Benzoyl-4-methylbenzenesulfonamide - Suchetan, P. A. (International Union of Crystallography, 2010)
In the title compound, C(14)H(13)NO(3)S, the N—H bond in is anti to the C=O bond. The dihedral angle between the two aromatic rings is 79.4 (1)°. In the crystal, molecules are linked by N—H⋯O hydrogen bonds, generating C(4) chains.